Russian Strategy Towards New Gas Producers (Syria And The Eastern Mediterranean Countries) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The discoveries of gas fields in the Eastern Mediterranean region led to many regional reactions; between those who welcomed it, and between expectations of the outbreak of conflicts over those fields and the overlapping of the influence of the major countries in the region. In the forefront: Russia and the states The United States of America, the European Union, Syria, Turkey, Lebanon and Palestine.For imposing its influence in the region, Russia has strengthened its foreign strategy, so it has developed advanced and connected infrastructure, as well as the establishment of external transport networks of all kinds, starting with rail transport, to maritime transport via giant tankers, and ending with transportation through complex networks of pipes.This research sheds light on the new gas discoveries in the Eastern Mediterranean countries and their economic and geopolitical impact on the relations of the major countries with the region. The study aimed to look at the reality of the energy war that the region is witnessing and its role in shaping future international policies and strategies. The study used the descriptive analytical approach to describing the true picture behind the strategies of the state's parties that were discussed, indicating the impact of invasive discoveries in drawing these strategies.The study concluded that the Middle East region embraces the most important wealth and the most intense battles. As none of the parties can work alone to end the conflict politically or militarily, but requires coordination on the level of international interests for each party, given that the region is only an arena that hosts a set of goals and interests the opposing major countries of the world.